[PP.04.19] LEFT ATRIUM VOLUME INDEX AND RISK PROFILE IN HYPERTENSIVE PATIENTS WITH ACUTE MYOCARDIAL INFARCTION. (September 2017) - Toader, D.; Popescu, M.; Oprian, A.; Musetescu, R.
Abstract : Objective: The left atrium volume index (LAVi) is a recognized prognostic marker in conditions as heart failure, myocardial infarction and atrial fibrillation. Dilatation of left atrium (DLA) in the absence of chronic arrhythmia, mitral valve disease or heart transplantation, is marker of chronic elevation of left atrium pressure. Numerous epidemiological studies have shown that the presence of arterial hypertension increases the risk of coronary heart disease especially in at risk populations. LA enlargement in hypertensive patients is related to overweight, diabetes and metabolic syndrome. Aim of the study was to find the presence of risk factors among the hypertensive patients with acute myocardial infarction (AMI) and the correlation with LAVi. Design and method: A number of 98 hypertensive patients (56 males and 42 females), aged 41- 85 years, admitted with ST-segment elevation AMI were evaluated during the first week of hospitalization before discharge by: clinical and laboratory examination, 12 lead standard ECG. LAVi echocardiographic measurement was made using disk summation algorithm, tracing endocardial borders in apical four and two chamber view and indexing by body surface area; cut off value was 34 ml/m 2 . Results: 1. In lot of study 57, 14% were males (78, 57% DLA) and 42, 86% females (73, 82% DLA). 2. Most of patients were aged 60–69 years: 34 patients (67, 83% DLA). 3. Looking for age and sex distribution of patients, in all groups male sex was dominant: highest incidence between 50–59 years group: 71, 42%, followed by 69–69 years group age: 55, 88%. 4. Most of patients: 56, 12% were stage 3 of hypertension (81, 81% DLA) 5.68, 36% of patients were diabetics (74, 62% DLA) 6. Obesity was found in 68, 36% of hypertensive patients with AMI. (73, 13% % DLA). 7. Dyslipidemia was found in 77, 55% of patients (66, 31% DLA) 8. Smoking was present in 53, 06% of patients. (76, 92% DLA when patients associated supplementary this risk factor) Conclusions: 1. We found an association between risk factors as: male sex, age, obesity, dyslipidemia, the level of blood pressure, diabetes, and smoking and the incidence of AMI in hypertensive patients. 2. In hypertensive patients with AMI a correlation between and risk factors and left atrium enlargement was present.